Histopathologic, immunoperoxidase and immunofluorescent examinations on natural cattle pneumonia originated from Parainfluenza type 3, Respiratory Syncytial virus, Adenovirus type 3 and Herpesvirus type 1 - Ceribasi, A. O.; Ozkaraca, M.; Ceribasi, S.; Ozer, H. (Ecole Nationale Veterinaire Toulouse, 2014)
The aim of this study to was determine Parainfluenza type 3 (PI3), Respiratory Syncytial virus (BRSV), Bovine Adenovirus type 3 (BAV3) and Bovine Herpesvirus type 1 (BHV1) antigens using direct fluorescent antibody technique (DFAT) and immunoperoxidase (IP) staining of frozen and formalin-fixed paraffin-embedded tissues in pneumonic lungs of cattle. For this purpose; the lungs of 2742 male cattle, which were raised in the farms in Elazig and surrounding areas and brought to the abattoir for slaughtering between January and December 2011, were examined. The macroscopic findings in 263 (9.59%) lungs, which pneumonia was detected only in apical and cardiac lobes, were recorded. Mild (65.02%), moderate (28.14%) and severe (6.84%) consolidations were detected in the pneumonic cases. Pneumonia were microscopically classified as catarrhal-purulent (32.32%), interstitial (45.25%), fibrinous (16.35%) and granulomatous (6.08%). A total of 247 lungs with pneumonia excluding those with granulomatous pneumonia were examined for PI3, BRSV, BAV3 and BHV1 viral antigens by IP and DFAT. PI3, BRSV, BAV3 and BHV1 antigens determined in natural pneumonia cases of cattle were found to be 6.88%, 3.64%, 5.26% and 2.43% by IP method and 10.53%, 6.07%, 6.88% and 4.45% by DFAT, respectively. It can be concluded that these viruses might have important role in the pathogenesis of pneumonia in cattle. In addition, DFAT and IP technique may be used for definitive diagnosis as valuable methods when the difficulties in the determination of specific histologic lesions in natural cattle pneumonia originated from PI3, BRSV, BAV3 and BHV1 antigens were considered. When all the data were considered overally, it can be suggested that there is an urgent need to take necessary measures in order to control and prevent these infections in the country.
Keywords: Parainfluenza type 3; Respiratory Syncytial virus; Bovine Adenovirus type 3; Bovine Herpesvirus type 1; immunoperoxidase; immunofluorescent; histopathology; pneumonie; cattle